Higgs-portal dark matter in Brane-world cosmology - Taoli Liu; Nobuchika Okada; Digesh Raut (European Physical Journal C: Particles and Fields)
Abstract The Higgs-portal scalar dark matter (DM) model is a simple extension of the Standard Model (SM) to incorporate a DM particle to the SM, where a $$Z_2$$ Z 2 -odd real scalar field is introduced as a DM candidate. We consider this DM model in the context of 5-dimensional brane-world cosmology, where our 3-dimensional space is realized as a hyper-surface embedded in 4-dimensional space. In the setup, all the SM and DM fields reside on the hyper-surface while graviton lives in the bulk. We consider two well-known brane-world cosmologies, namely, the Randall–Sundrum (RS) and the Gauss–Bonnet (GB) brane-world cosmologies, in which the standard Big Bang cosmology is reproduced at low temperatures below the so-called “transition temperature” while at high temperatures the expansion law of the universe is significantly modified. Such a non-standard expansion law directly impacts the prediction for the relic density of the Higgs-portal DM. We investigate the brane-world cosmological effects and identify the allowed model parameter region by combining the constraints from the observed DM relic density, and the direct and indirect DM detection experiments. It is well-known that only DM masses in the vicinity of half the Higgs boson mass are allowed in the Higgs-portal scalar DM model. We find that the allowed parameter region becomes more severely constrained and even disappears in the RS cosmology, while the GB cosmological effect significantly enlarges the allowed region. Upon discovering Higgs-portal DM, we can determine transition temperature in the GB brane-world cosmology.